ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN UMKM JAYA PONSEL - Sidik, Dena Purnama; Halimah, Diniar; Andriyani, Desi; Suharniati, Suharniati; Kamilah, Nurul (LPPM Universitas Nusa Mandiri, 2024)
Micro, Small, and Medium Enterprises (UMKM) play a crucial role in Indonesia's economy, particularly in providing employment opportunities and supporting local economic growth. Jaya Ponsel, an MSME operating in the mobile phone sales and repair sector, requires a financial performance evaluation to maintain business stability and growth. This study aims to assess Jaya Ponsel's financial performance through financial ratio analysis, covering liquidity, solvency, activity, and profitability, and to present the income statement and balance sheet for 2022 and 2023. The method used is a quantitative descriptive approach, with data sourced from the company's internal financial reports. The analysis results indicate that although there was a decline in some liquidity and activity ratios, Jaya Ponsel managed to improve its profitability. The current ratio decreased from 2.50 in 2022 to 2.20 in 2023, while the quick ratio dropped from 2.00 to 1.80. The increase in the debt-to-asset ratio and debt-to-equity ratio suggests greater reliance on debt. On the other hand, the profit margin on sales rose from 20% to 22%, ROI increased from 6.67% to 7.50%, and ROE improved from 11.11% to 12.63%. In conclusion, despite challenges in liquidity management and operational efficiency, Jaya Ponsel successfully maintained and enhanced its profitability. These findings provide valuable insights for management to optimize financial and operational strategies moving forward.